“It Changes Everything”: Family Members’ Experiences of Childhood Cancer - Davies, Jenny (Curtin University, 2024)
Inspired by her own experience of having daughter diagnosed with childhood cancer and determined to turn her own experience into something which could help others, this PhD thesis provides an insightful exploration of families’ experiences of childhood cancer. It sheds light on the experiences of pregnant mothers of children with cancer, the multifaceted impacts of COVID-19 and explores the experiences of fathers, siblings and grandparents. This research will directly inform improvements in supports services